2012
DOI: 10.1371/journal.pone.0031223
|View full text |Cite
|
Sign up to set email alerts
|

Persistence versus Escape: Aspergillus terreus and Aspergillus fumigatus Employ Different Strategies during Interactions with Macrophages

Abstract: Invasive bronchopulmonary aspergillosis (IBPA) is a life-threatening disease in immunocompromised patients. Although Aspergillus terreus is frequently found in the environment, A. fumigatus is by far the main cause of IBPA. However, once A. terreus establishes infection in the host, disease is as fatal as A. fumigatus infections. Thus, we hypothesized that the initial steps of disease establishment might be fundamentally different between these two species. Since alveolar macrophages represent one of the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 91 publications
8
95
2
Order By: Relevance
“…1B). Previous studies have shown that innate phagocytes can kill A. fumigatus conidia over time in vitro (34). Therefore, to determine if conidial killing accompanied immunocompetent larval survival in vivo, pools of 20 larvae were homogenized at 0, 1, 3, 5, and 7 days postinfection (dpi) to assess the average fungal burden throughout the course of infection.…”
Section: Resultsmentioning
confidence: 99%
“…1B). Previous studies have shown that innate phagocytes can kill A. fumigatus conidia over time in vitro (34). Therefore, to determine if conidial killing accompanied immunocompetent larval survival in vivo, pools of 20 larvae were homogenized at 0, 1, 3, 5, and 7 days postinfection (dpi) to assess the average fungal burden throughout the course of infection.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the conidial melanin in the A. fumigatus virulence has been studied by using either melanin ghosts or the pigmentless mutant, wherein the PKSP gene, which encodes a protein involved in the first step of melanin biosynthesis, has been deleted (4,9,(16)(17)(18)(19), These reports demonstrated that melanin protects the conidia against reactive oxygen species, masks the recognition of various A. fumigatus pattern-associated molecular patterns, inhibits macrophage apoptosis and phagolysosome fusion, and attenuates the host immune response. All of these functions of melanin contribute to the increased survival of conidia in macrophages and promote the dissemination of A. fumigatus within the host.…”
mentioning
confidence: 99%
“…This species is the main etiologic agent of pulmonary and systemic aspergillosis in immunocompromised persons. It may occur as an opportunistic pathogen or as an allergen, moreover, it is found on the list of harmful biological agents found in the workplace [23,[34][35][36]. However, only exposure to high levels of airborne filamentous fungi (e.g., 10 10 spores/m 3 ) associated with bioaerosols may result in sickness partly caused by mycotoxins [37].…”
Section: Discussionmentioning
confidence: 99%